EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN PRESTASI SISWA SMK - Muhamad Kamaludin; Dadang Hafid; Asep S. Setyadin; Dede Angga Maulana (JESA-Jurnal Edukasi Sebelas April, 2024)
This study aims to evaluate the application of the Problem Based Learning (PBL) model in improving student learning outcomes in the subject of Basic Automotive Engineering Works (PDTO) on hand tools material in class X TKR 1 SMK Negeri Situraja. The main problem identified was the lack of interest, enthusiasm, and attention of students during learning. The PBL model was applied to improve student motivation and learning outcomes. Data analysis showed that the use of PBL was very efficient, as evidenced by the results of the t-test which showed tcount = 26.58, greater than ttable = 23.267, so the alternative hypothesis was accepted. In addition, the average pretest score increased from 41.5 to 77.3 in the posttest, indicating a significant increase in learning outcomes. The results of this study indicate that the PBL model can effectively improve student learning achievement.